Facial Expression Recognition Using Temporal Templates - Mahdi Bejani; Davood Gharavian; Nasrollah Charkari (Majlesi Journal of Electrical Engineering)
To make humanâcomputer interaction (HCI) more natural and friendly, it would be beneficial to give computers the ability to recognize situations the same way a human does. Naturally, people use a spontaneous combination of face, body gesture and speech to express their feelings. In this paper we simulate human perception of emotion with emotion related information from facial expression. Facial expression recognition based upon ITMI and QIM which can be seen as an extension to temporal templates. The system was tested on two different databases, the eNterfaceâ05 and the Cohn-Kanade face database and the recognition accuracy of our systems ,71.8 % on Cohn-Kanade and 39.27% on eNterfaceâ05, compared to the published results in the literature.